THE IMPORTANCE OF FREE AND CRITICAL THINKING IN HUMAN BEHAVIOR AND DECISION-MAKING PROCESSES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the concept of “thought” as the foundation of philosophical reasoning. It analyzes the historical development and theoretical significance of thought in the formation of philosophical systems, highlighting its role in logic, cognition, and decision-making processes. The study explores classical and modern philosophical perspectives, emphasizing how thought serves as the basis for understanding reality, knowledge acquisition, and rational analysis. The findings demonstrate that thought is not only the core of philosophical reflection but also a crucial mechanism for structuring knowledge and guiding intellectual inquiry.